2007
DOI: 10.1111/j.1399-6576.2007.01368.x
|View full text |Cite
|
Sign up to set email alerts
|

Who is responsible for operating room management and how do we measure how well we do it?

Abstract: The structure of the daily operative management of an operating room needs redefining. There should be more focus on collaboration and communication between the care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 17 publications
0
29
0
5
Order By: Relevance
“…Nurse managers rarely supervised any other professionals (e.g. physicians) than their own nurses (Marjamaa & Kirvelä, ) and challenges existed when managing other professionals (Martin & Waring, ). Sharing of responsibility between nurse managers and physicians should be clear to everyone (Marjamaa & Kirvelä, ; Martin & Waring, ).…”
Section: Key Issuementioning
confidence: 99%
“…Nurse managers rarely supervised any other professionals (e.g. physicians) than their own nurses (Marjamaa & Kirvelä, ) and challenges existed when managing other professionals (Martin & Waring, ). Sharing of responsibility between nurse managers and physicians should be clear to everyone (Marjamaa & Kirvelä, ; Martin & Waring, ).…”
Section: Key Issuementioning
confidence: 99%
“…The operating theatre represents one of the most critical hospital units, both in patient safety and financial terms [12,13]. The team has chosen the topic of operating room management because of an urgent need to deliver high quality care with limited resources and the correct management of operating theaters represents an important step towards achieving this.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work showed that anesthesiologists perceive OR management to be an integral part of their professional work (Marjamaa and Kirvela, 2007;Larsson et al, 2003). As reviewed in the Introduction, statistical methods are needed for good OR management decisions, and misconceptions that good decisions can be made absent statistical methods are due to psychological biases.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesiologists are integrally involved in operating room (OR) management (Marjamaa and Kirvela, 2007), and describe coordination of surgical suites and smooth patient flow as part of their professional work (Larsson, Holmström, and Rosenqvist, 2003). However, OR management differs from clinical anesthesia in that statistical literacy and reasoning are needed to make good decisions.…”
Section: Introductionmentioning
confidence: 99%